Indicazioni all’utilizzo del concentrato midollare nella chirurgia endoscopica del morbo di Haglund - Rota, A.; De Santis, P.; Rota, P. (Lo Scalpello - Journal, 2019)
AUTOLOGOUS BONE MARROW-DERIVED MESENCHYMAL STEM CELLS (MSCS) INDICATIONS FORENDOSCOPIC TREATMENT OF HAGLUND’S SYNDROMESurgical treatment in Haglund’s deformity involves removal of the dorsolateral part of the calcaneus up to theinsertion of the Achilles tendon and the inflamed retrocalcaneal bursa. Traditionally treated with open surgery, afterfailure of the conservative treatment, there is increasing interest in a more minimally invasive approach to reducecomplications and improve the rate and ease of recovery. The poor results of open surgical treatment may be due toincorrect indication for surgery, incomplete or aggressive bone resection, fibrosis, chronic tendinopathy, painful scarsand numbness in the heel. The minimally invasive surgical technique by an endoscopic calcaneoplasty (ECP) could bean option to overcome some of these problems. The endoscopic technique include: patient prone, peripheralanesthesia, standard instruments. We have used the autologous bone marrow-derived mesenchymal cells (MSCs)obtained from iliac crest for severe Achilles tendonosis. The purpose of our study was to describe management ofHaglund’s Syndrome, evaluate the effectiveness of a minimally invasive procedure, demonstrating the validity as wellin the revisions of the open treatments in athletes. Adequate relief of symptoms is considered to be dependant onremoving any osseous irritation to the Achilles insertion (bone resection), fibrolysis and using autologous bonemarrow-derived Mesenchymal stem cells (MSCs) for severe Achilles tendonosis.